TIPE DAN POLA KLAUSA SUBORDINATIF BAHASA INDONESIA - Ratna Djuwita Bandono (Fakultas Seni Rupa dan Desain ITB, 2010)
The research deals with Indonesian subordinative clause type and pattern. It focuses on construction, function, distribution and meaning of clauses. The data are obtained from non-fiction written texts. The method is synchronic descriptive. The method of analysis is distributional with the technique of analysis that includes substitutions, permutations, and deletions. The underpinning theories are applied eclectically reffering to Ramlan (1981), Kridalaksana (1986), Djajasudarma (1993, 1997,1999), Tadjuddin (1994, 2006), Sibarani (1994). Alwi dkk. (2000), Badudu (2002), and Chaer (2009). In addition, the theories of comphrehentions in English are employed by reffering to Halliday (1976), Quirk et al. (1983), and Brown and Miller (1999). Based on the study, it can be concluded that (1) subordinative clauses are clauses which are simultaneously with conjunctions to become constituent of compound sentences. Such constructions of subordinative clauses consist of one elements (syntactical functions). (2) Subordinative clauses generally function as adverbs. They however can also function as objects or complements. These functions are resulted from the functions of verbs which are predicate elements of main clauses. (3) The subordinative clauses with the presences of conjunctions correlates to time, condition, purpose, consession, reason/cause, effect/result, and manner. Key words: clause, subordinative, type, and pattern